Pengaruh Pembelajaran Teks Rekon Terhadap Kemampuan Menulis Siswa Kelas IX - rozi, Moh Fakhrur; Edhi Wicalsono, Purnama (J-SES : Journal of Science, Education and Studies, 2025)
Abstract: This research aims to determine the effect of learning rekon texts on the writing abilities of class IX students. The research method used was quasi-experimental with a pretest-posttest design. The research subjects consisted of 30 class IX students at SMP Negeri Data were analyzed using statistical tests to measure significant differences between writing abilities before and after learning. The research results show that rekon learning texts have a significant positive influence on students' writing abilities, especially in mastering text structure and using appropriate language. Thus, rekon texts can be used as an effective medium in learning Indonesian at the junior high school level. Keywords: recon text, writing ability, learning, class IX students, quasi-experiment